AVES ATRAÍDAS POR RESÍDUOS SÓLIDOS NO ATERRO SANITÁRIO DE OLINDA - PE - Arruda, André Ribeiro de; Azevedo Júnior, Severino Mendes de; Larrazábal, Maria Eduarda de (Revista Nordestina de Zoologia, 2011)
The food supply and other characteristics of landfills have established an ecological relationship between birds and the environment. Understanding this relationship is important for a better understanding of the biology of these birds and the possible problems generated by this relationship. This research aimed to provide required data on the ecological aspect of the birds that use some form of landfill. The area has 19 hectares in total and eight acres dedicated to the disposal of waste. The vegetation is a scrub and bush. Data were collected from April to November 2010, with three monthly visits. The populations black vulture and of the cattle egret showed decline related to low rainfall, both also showed aggregate dispersion. Altogether 13 species were identified of families Ardeidae, Cathartidae, Falconidae, Charadriidae, Columbidae, Cuculidae, Tyranninae, Fluvicolinae Hirundinidae, and Passeridae. The 13 species have different dynamics and frequencies, however are equal with respect to the main use of the landfill, which is seen as a "great generator of food." Some species are further deepen in this relationship and found in the landfill, shelter and site to nesting, using vegetation or areas built for your done. There is thus an adaptive relationship of some species with the landfill.